2007
DOI: 10.1007/s00213-007-0952-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transdermal nicotine replacement on alcohol responses and alcohol self-administration

Abstract: Rationale-Nicotine replacement is commonly used to treat tobacco use in heavy-drinking smokers. However, few studies have examined the effect of nicotine replacement on subjective and physiological responses to alcohol and alcohol drinking behavior.Objective-The primary aim of this within-subject, double-blind study was to examine whether transdermal nicotine replacement (0 mg vs 21 mg/day) altered response to a low-dose priming drink and subsequent ad libitum drinking behavior.Materials and methods-Subjects (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 71 publications
(107 reference statements)
4
80
2
Order By: Relevance
“…Craving-related BOLD signals were obtained from the sham TMS sessions and regressed against the relative subjective craving level. The individual variation in the mOFC signal was significantly explained by the subjective variance in craving in both the immediate [F (1,8) = 13.4, P < 0.01] and delayed condition [F (1,8) = 7.2, P < 0.05] as shown in Fig. 2C, indicating that mOFC activity reflected the subjective valuation of drug-related stimuli.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Craving-related BOLD signals were obtained from the sham TMS sessions and regressed against the relative subjective craving level. The individual variation in the mOFC signal was significantly explained by the subjective variance in craving in both the immediate [F (1,8) = 13.4, P < 0.01] and delayed condition [F (1,8) = 7.2, P < 0.05] as shown in Fig. 2C, indicating that mOFC activity reflected the subjective valuation of drug-related stimuli.…”
Section: Resultsmentioning
confidence: 89%
“…Behavioral economists propose that drug cues increase the marginal utility of the drug, favoring the decision to consume (3,5,6). Indeed, cue-induced craving reflects the subjective value of drug use (7) and predicts drug-seeking behaviors (8,9), but is also amenable to self-control (6,10). Cue-induced craving is affected by a variety of contexts and events that impact self-control, such as perceived drug availability (11)(12)(13)(14), expectancy (15), stress (16), or intention to seek treatment (17).…”
mentioning
confidence: 99%
“…Other TTURC researchers are testing the potential value of mecamylamine, a nicotine antagonist, in the treatment of alcohol drinking. McKee, Krishnan-Sarin, Shi, Mase, and O'Malley (2006) are examining whether varenicline, a partial agonist, attenuates the adverse effect of alcohol on ability to resist smoking using a laboratory model developed in the TTURC and whether varenicline reduces alcohol drinking among heavy-drinking smokers using a paradigm in which benefi cial effects of NRT were demonstrated ( McKee, O'Malley, Shi, Mase, & Krishnan-Sarin, 2008 ).…”
Section: Key Fi Ndingsmentioning
confidence: 99%
“…A third important limitation is that differences in SR have been identified based on several other alcoholrelated risk factors, including gender (e.g., Luczak et al, 2002;Miller et al, 2009), race (Pedersen & McCarthy, 2013;Plebani et al, 2011), and cigarette smoking status (e.g., Cooney et al, 2001;McKee et al, 2008). However, study findings have been inconsistent, making it difficult to identify distinct profiles of risk associated with these demographic characteristics.…”
mentioning
confidence: 99%
“…Some studies have found that nicotine (administered via smoking, intranasally, or by transdermal patch) reduces craving for alcohol (Cooney et al, 2001) and attenuates the experience of intoxication and/or reduces ad libitum drinking (McKee et al, 2008), whereas others suggest that nicotine use increases subjective intoxication and craving (Kouri et al, 2004) and, for men, results in increased self-administration (Acheson et al, 2006).…”
mentioning
confidence: 99%